Allometric variation in the genus Steinmanella (Trigonioida, Bivalvia) from the Lower Cretaceous of the Neuquén Basin (west-central Argentina) - Milla Carmona, Pablo Sebastián (2019)
Because of the outstanding diversity and disparity they reached during the Mesozoic, the paleobiology of trigoniid bivalves has attracted considerable interest. In this work, we assess the patterns of allometric variation within the genus Steinmanella (Myophorellinae, Trigonioida) as it occurs in the lower Valanginian - upper Hauterivian (Lower Cretaceous) of the Neuquén Basin (west-central Argentina). A sample of 236 specimens belonging to 7 species of Steinmanella (namely, S. quintucoensis, S. subquadrata, S. curacoensis, S. caicayensis, S. pehuenmapuensis, S. transitoria and S. vacaensis), was digitized in three dimensions, and variation in two prominent external morphological characters, general geometry and sculpture, was subsequently analyzed. Shell surface shape and size were measured by means of 3D geometric morphometrics, whereas sculpture was quantified using counts of ribs and nodes. The trajectories of the studied species through different size categories (intended to represent meaningful ontogenetic stages) were compared using phenotypic trajectory analysis. Our results show that early and late growth changes differ in style across species. The former seems to be far more plastic, being characterized by changes in the direction and magnitude of the allometric trajectory in the shell surface and sculpture morphospaces, respectively. On the other hand, late growth seems to be more conserved and channelled, showing more infrequent changes which mainly involve the magnitude of the trajectory across the surface morphospace. Therefore, the distinctive features of each species would had been acquired early in life, with later changes involving a general trend towards elongation of the shell, thus challenging the view that early development is more conserved in evolution. These findings can have important implications for the evolution of Steinmanella, as heterochronic processes acting upon ontogenetic variation is thought to be a major driver of bivalve evolution.